Contextualizing communities in an instructional improvement initiative: exploring STEM faculty engagement in teaching-related conversations - Ellen Marie Aster; Jana Bouwma-Gearhart; Kathleen Quardokus Fisher (Disciplinary and Interdisciplinary Science Education Research, 2021)
Abstract A frequently cited strategy for fostering science, technology, engineering, and mathematics (STEM) instructional improvements is creating communities where faculty can share and learn evidence-based teaching practices. Despite research-documented benefits, little is known about why (and with whom) faculty engage in teaching-related conversations, including those fostered by initiative communities. We explored how STEM faculty engage in teaching-related conversations, via analysis of faculty interviews and discussion networks, to identify factors potentially influencing teaching-related conversations over the life of an initiative. Our results suggest aspects that might inhibit STEM faculty from engaging in teaching-related conversations, including: 1) faculty members’ autonomy with teaching practices; 2) faculty members’ varied interests in teaching improvements; 3) varied degrees of support to engage in teaching-related conversations; and 4) a lack of inclusive and non-judgmental spaces to talk about teaching. We suggest that those fostering STEM faculty communities consider working with others across the institution to map the instructional improvement opportunities faculty may already take part in and attend to areas lacking support. Initiative leaders and designers should also elicit and build off faculty members’ teaching-related knowledge and concerns. We further suggest making conversational spaces inclusive and safe, to help faculty honestly share teaching-related challenges and insights. We recommend creating and fostering spaces that bring faculty together across department boundaries. Our study echoes prior research by drawing attention to administrative support for instructional improvement initiatives, which can foster and sustain opportunities for faculty to talk about teaching and learn instructional improvements.